Organic-inorganic composite polymer electrolyte and all-solid-state battery comprising same

By using organic and inorganic composite polymer electrolytes in lithium secondary batteries, combining flame-retardant polymers and inorganic salts, the liquid leakage and flammability problems of liquid electrolytes are solved, and the safety and life of the battery are improved, ensuring that Stability of battery performance.

CN119153770APending Publication Date: 2024-12-17SK ON CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410762950.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-06-12
Filing Date
2024-06-13
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The liquid electrolytes in existing lithium secondary batteries have problems of liquid leakage and flammability. The polymer electrolytes have failed to completely solve the risk of fire and lack the flame retardancy and functional inorganic salts.

Method used

Using organic inorganic composite polymer electrolytes, including flame-retardant polymers and inorganic salts, and a flame-retardant inorganic salt with a shear modulus of 7 to 60 GPa, the F free radical or CO2 is generated by thermal decomposition to inhibit combustion, and in the electrolyte Form polymer networks to improve flame retardancy and physical properties.

Benefits of technology

Effectively inhibit the growth of lithium dendrites, prevent battery short circuits and fires, improve battery safety and life, and maintain good ion conductivity and battery performance in non-aqueous electrolytes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153770A_ABST
    Figure CN119153770A_ABST
Patent Text Reader

Abstract

The present disclosure relates to an organic-inorganic composite polymer electrolyte and an all-solid-state battery including the same, and provides an organic-inorganic composite polymer electrolyte including a flame retardant polymer and a flame retardant inorganic salt having a shear modulus of 7 to 60 GPa, and an all-solid-state battery including the organic-inorganic composite polymer electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an organic-inorganic composite polymer electrolyte and an all-solid-state battery comprising the organic-inorganic composite polymer electrolyte. Background Art

[0002] Generally, lithium secondary batteries can be manufactured using a positive electrode and a negative electrode including an electrode active material capable of inserting / releasing lithium ions, and an electrolyte as a transport medium for lithium ions. As the electrolyte, a liquid electrolyte is mainly used, especially an ion-conductive organic liquid electrolyte in which a salt is dissolved in a non-aqueous electrolyte solvent.

[0003] However, such liquid electrolytes have the risk of electrolyte leakage and may cause safety problems of the device such as fire and explosion due to the high flammability of the non-aqueous electrolyte solvent.

[0004] Therefore, secondary batteries using polymer electrolytes that do not have the risk of leakage have been proposed. Generally, the polymer electrolytes are produced by impregnating a polymer matrix obtained by polymerizing a polymerizable monomer and a polymerization initiator with an electrolyte solution containing an electrolyte salt and an organic solvent.

[0005] Although such a secondary battery including a polymer electrolyte provides an effect of improving battery safety, the polymer electrolyte still includes a non-aqueous electrolyte solvent, and thus the problem of fire is not completely solved and is limited.

[0006] In addition, polymer electrolytes generally do not include flame retardant polymers, and electrolytes generally do not include functional inorganic salts.

[0007] Although there are many reports on organic-inorganic polymer electrolyte technologies that partially include inorganic substances and polymers, the inorganic substances included in these technologies are intended to improve the physical properties of the polymer electrolyte and do not have the purpose of ensuring the flame retardancy of the electrolyte. Summary of the invention

[0008] The present disclosure intends to provide an organic-inorganic composite polymer electrolyte capable of improving the safety and life characteristics of a lithium secondary battery.

[0009] Specifically, the present disclosure, as an implementation example, intends to provide an electrolyte that can improve the flame retardancy of a polymer electrolyte and enhance the physical properties of the electrolyte, thereby preventing battery short circuits and inhibiting the growth of lithium dendrites.

[0010] As an implementation example, the present disclosure may provide an organic-inorganic composite electrolyte, wherein the organic-inorganic composite polymer electrolyte includes a flame retardant polymer and a flame retardant inorganic salt having a shear modulus of 7 to 60 GPa.

[0011] The flame retardant polymer may include at least one selected from the group consisting of phosphorus polymers, phosphazene polymers, fluorinated polymers, and ionic polymers.

[0012] The phosphorus-based polymer may include at least one selected from the group consisting of phosphates, phosphonates, and phosphinates.

[0013] The phosphorus-based polymer may include a structural unit derived from a compound represented by the following Chemical Formula 1.

[0014]

Chemical formula 1

[0015]

[0016] In the chemical formula 1, L 1 To L 3 are each independently a direct bond; or a substituted or unsubstituted C1-C 20 Alkyl, R 1 To R 3 Each of them is independent of the other and at least one of them is a functional group having a double bond between carbon atoms, and the others are independently of the other and are hydrogen, a substituted or unsubstituted hydrocarbon group.

[0017] It can be that, in the chemical formula 1, R 1 To R 3 Each of the functional groups is independent of the other and at least one of the functional groups is selected from the group consisting of acrylate, methacrylate, cyanoacrylate, vinyl acrylate, vinyl, allyl, and vinyl ether.

[0018] The hydrocarbon group may be selected from substituted or unsubstituted C1-C 20 Alkyl, substituted or unsubstituted C2-C 20 Alkenyl and substituted or unsubstituted C6-C 20 Aryl.

[0019] The phosphazene polymer may include at least one selected from the group consisting of linear phosphazenes and cyclic phosphazenes.

[0020] The flame retardant polymer may further include a structural unit derived from a network polymer structure derivative having two or more reactive functional groups.

[0021] It may be that the network polymer structure derivative includes a compound represented by the following Chemical Formula 2:

[0022]

Chemical formula 2

[0023]

[0024] In the chemical formula 2, R 4 To R 6 Each independently selected from the group consisting of hydrogen, acrylate, methacrylate, cyanoacrylate, vinyl acrylate, vinyl, allyl and vinyl ether, R 4 To R 6 At least two of the above are selected from the group consisting of acrylate, methacrylate, cyanoacrylate, ethylene acrylate, vinyl and vinyl ether groups, wherein R 7 is selected from hydrogen, substituted or unsubstituted C1-C 20 Alkyl, substituted or unsubstituted C2-C 20 Alkenyl and substituted or unsubstituted C6-C 20 Aryl.

[0025] The flame retardant polymer may account for 50% by weight or less of the total weight of the organic-inorganic composite polymer electrolyte.

[0026] The flame retardant inorganic salt may generate F radicals or CO 2 by thermal decomposition.

[0027] The solubility of the flame retardant inorganic salt in water may be 1.5 g / 100 mL or less.

[0028] The flame retardant inorganic salt may have a particle size of 5 nm to 50 μm.

[0029] The flame retardant inorganic salt may be selected from the group consisting of metal fluorides and carbonate compounds.

[0030] The flame retardant inorganic salt may include fluoride or carbonate of Li or Na.

[0031] The flame retardant inorganic salt may be less than 10% by weight of the total weight of the organic-inorganic composite polymer electrolyte.

[0032] As another implementation example, the present disclosure provides an all-solid-state battery, which includes a negative electrode, a positive electrode, and any one of the organic-inorganic composite polymer electrolytes described above located between the negative electrode and the positive electrode.

[0033] The organic-inorganic composite polymer electrolyte may have a concentration gradient of the flame retardant inorganic salt.

[0034] The flame retardant inorganic salt may be present in a larger amount by weight at the center than at the surface in the thickness direction of the organic-inorganic composite polymer electrolyte.

[0035] According to the present disclosure, even if a non-aqueous electrolyte is included, the flame retardancy of the electrolyte can be improved, thereby suppressing or even preventing fire and thermal runaway when the inside of the polymer electrolyte solid state battery is overheated.

[0036] In addition, the organic-inorganic composite polymer electrolyte disclosed in the present invention can inhibit the growth of lithium dendrites, thereby preventing battery short circuits and further improving battery safety, thereby improving battery life.

[0037] The organic-inorganic composite electrolyte disclosed in the present invention can be widely used in electric vehicles, battery charging stations, and other green technology fields such as solar power generation and wind power generation using batteries. In addition, the organic-inorganic composite electrolyte disclosed in the present invention can be used in eco-friendly electric vehicles (Electric Vehicle) and hybrid vehicles (hybrid vehicles) for suppressing air pollution and the release of greenhouse gases to prevent climate change. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The photographs are taken to show whether the organic-inorganic composite polymer electrolytes manufactured in Examples 1, 2 and Comparative Examples 2, 3 have fluidity. (a) is a photograph of a transparent container containing the organic-inorganic composite polymer electrolyte being placed normally, and (b) is a photograph of the transparent container being placed upside down.

[0039] Figure 2 is shown at 1.5 mA / cm 2 And a graph showing the voltage change caused by the electrodeposition and removal of lithium over time when the lithium symmetric button battery cells using the electrolytes of Examples 1, 2 and Comparative Examples 1 to 4 are driven under 2 hours conditions. DETAILED DESCRIPTION

[0040] An embodiment provides an organic-inorganic composite polymer electrolyte, which includes a flame retardant polymer and a flame retardant inorganic salt, wherein the shear modulus of the flame retardant inorganic salt is 7 to 60 GPa. The electrolyte according to the present disclosure may be an organic-inorganic composite polymer electrolyte including a flame retardant inorganic salt, an electrolyte salt and a non-aqueous solvent in a flame retardant polymer matrix.

[0041] In the present disclosure, the flame retardancy indicates the performance of a sample that burns when in contact with a flame (ignition source) but prevents or suppresses the generation of flames and combustion when the flame is removed. The flame retardancy can be evaluated by the time it takes for the sample to be extinguished after a blowtorch is used to supply a flame of a certain heat for more than 1 second to ignite the sample and then the blowtorch is removed. The shorter the time required to extinguish the fire, the better the flame retardancy.

[0042] Specifically, the flame retardant polymer can be a polymer that is made into a glass fiber impregnation type or a self-supporting film form with a diameter of 19 mm, and is ignited by supplying a certain amount of heat to it with a blowtorch for more than 1 second, and then the blowtorch is removed, and the polymer extinguishes the fire within 2 seconds, specifically within 1 second, and more specifically within 0.5 seconds. In addition, the flame retardant inorganic salt can be an inorganic salt that extinguishes the fire within 2 seconds, specifically within 1 second, and more specifically within 0.5 seconds when igniting more than 0.1g of powder as above. The flame retardancy of the electrolyte can be improved by adding such a flame retardant polymer and a flame retardant inorganic salt to the organic-inorganic composite electrolyte.

[0043] The flame retardant polymer is a flame retardant monomer polymerized into a solid state, and can be provided as a polymer matrix. Therefore, the polymer matrix may have low fluidity in the electrolyte, and in the case of including an electrolyte solvent, it may not hinder the movement of lithium ions in the electrolyte.

[0044] In the present disclosure, the flame retardant polymer may use a polymer having a functional group capable of capturing free radicals to interrupt combustion. The flame retardant polymer may be a polymer of a monomer having at least one double bond, and is not limited thereto. For example, it may include a phosphorus polymer selected from phosphoric acid esters, phosphonic acid esters, and phosphinates; a phosphazene polymer including linear phosphazenes and cyclic phosphazenes; a fluorinated (C1-C 20 ) alkyl, fluorinated ether, fluorinated ester and fluorinated carbonate fluorinated polymer; and at least one of the group consisting of imidazolium, pyrrolidinium, piperidinium, pyridinium, ammonium and phosphonium ionic polymers.

[0045] Specifically, the flame retardant polymer may include a structural unit derived from a monomer having at least one double bond. As long as it is a monomer having a double bond, the monomer having at least one double bond is not particularly limited. Specifically, it may include a double bond as a polymerizable group. For example, a functional group having a double bond between carbons may be included at the end as a polymerizable group. Specifically, it may include at least one selected from the group consisting of an acrylate group, a methacrylate group, a cyanoacrylate group, an ethylene acrylate group, a vinyl group, an allyl group and a vinyl ether group as a polymerizable group.

[0046] The monomer having at least one double bond may include 1 to 3 polymerizable groups, specifically, may have 1 or 2 polymerizable groups.

[0047] For example, the monomer having at least one double bond may include a phosphorus (P) element, for example, may include a phosphorus group.

[0048] Specifically, the monomer having at least one double bond can be represented by the following chemical formula 1, and the phosphorus-based flame retardant polymer can be generated by polymerization of the monomer:

[0049]

Chemical formula 1

[0050]

[0051] In the chemical formula 1, L 1 To L 3 can be independently a direct bond; or a substituted or unsubstituted C1-C 20 alkyl.

[0052] In addition, in the chemical formula 1, R 1 To R 3 Independent of each other, R 1 To R 3 At least one of them may be a functional group having a double bond between carbons, and the rest may be independently hydrogen, a substituted or unsubstituted hydrocarbon group.

[0053] Specifically, in the chemical formula 1, R 1 To R 3 Independent of each other, R 1 To R 3 At least one of the functional groups having a double bond between carbon atoms may be, for example, an acrylate group, a methacrylate group, a cyanoacrylate group, an ethylene acrylate group, a vinyl group, an allyl group, a vinyl ether group or a combination thereof.

[0054] In one aspect, the substituted or unsubstituted hydrocarbon group is not limited thereto, and can be a substituted or unsubstituted C1-C 20 Alkyl, substituted or unsubstituted C2-C 20 Alkenyl and substituted or unsubstituted C6-C 20 Aryl.

[0055] The non-aqueous solvent included in the secondary battery generally undergoes thermal decomposition as the battery temperature rises, thereby generating highly reactive free radicals such as OH· and H· through a chain combustion reaction as shown below, which are simultaneously burned. In addition, as mentioned above, the free radical generation reaction is an exothermic reaction, so a chain combustion reaction of the non-aqueous solvent is generated, which can cause the battery to explode and catch fire.

[0056] RH→R·+H·

[0057] H·+O2→HO·+O·

[0058] HO·+H2→H·+H2O

[0059] O·+H2→HO·+H·

[0060] However, when the flame retardant polymer as described above is included, radicals are released from the flame retardant polymer, and the released radicals capture H·radicals or OH·radicals having high activity generated during combustion of the non-aqueous solvent, thereby interrupting combustion.

[0061] Specifically, when the flame retardant polymer is a phosphorus-based polymer, when the non-aqueous solvent burns, P radicals are released from the phosphorus monomers that constitute the phosphorus-based polymer. The released P radicals capture the H radicals or OH radicals generated in the combustion of the non-aqueous solvent, thereby inhibiting or even interrupting further combustion.

[0062] In the present disclosure, the flame retardant polymer may form a matrix in the polymer electrolyte layer, and the flame retardant polymer may further include a structural unit derived from a network polymer structure derivative.

[0063] The flame retardant polymer also includes a structural unit derived from a network polymer structure derivative, so that an organic-inorganic composite polymer electrolyte with non-fluidity can be manufactured more easily.

[0064] The network polymer structure derivative is different from the monomer having at least one double bond and can be a compound having more than two reactive functional groups, specifically, a compound having 2 to 4 reactive free radicals, and more specifically, a compound having 3 reactive functional groups.

[0065] Specifically, the network polymer structure derivative may be, for example, a compound having a structure such as the following Chemical Formula 2:

[0066]

Chemical formula 2

[0067]

[0068] In the chemical formula 2, R 4 To R 6 Each independently selected from the group consisting of hydrogen, acrylate, methacrylate, cyanoacrylate, vinyl acrylate, vinyl, allyl and vinyl ether, R 4 To R 6 At least two of the above are selected from the group consisting of acrylate, methacrylate, cyanoacrylate, ethylene acrylate, vinyl and vinyl ether. 4 To R 6 can be the same or different from each other, and two or more can be functional groups having double bonds between carbon atoms, for example, R 4 To R 6 They may all be functional groups having double bonds between carbon atoms.

[0069] In the chemical formula 2, the R 7 It can be hydrogen, a substituted or unsubstituted hydrocarbon group, and the hydrocarbon group can be selected from substituted or unsubstituted C1-C 20 Alkyl, substituted or unsubstituted C2-C 20 Alkenyl and substituted or unsubstituted C6-C 20 Aryl, specifically, can be C1-C 10 alkyl.

[0070] The flame retardant polymer includes structural units derived from a network polymer structure derivative, thereby forming a polymer network with structural units derived from the monomer having at least one double bond (specifically, the compound represented by the chemical formula 1), which can more easily inhibit the flow of the organic-inorganic composite polymer electrolyte.

[0071] Although not limited to this, when a small amount of a monomer having at least one double bond containing the above-mentioned polymerizable group (specifically, a monomer including 1 polymerizable group, more specifically, a compound represented by the chemical formula 1) is used, the flame retardant polymer also includes a structural unit derived from a network polymer structure derivative, thereby being able to more effectively control the fluidity of the organic-inorganic composite polymer electrolyte.

[0072] For example, when the organic-inorganic composite polymer electrolyte contains a small amount of the above-mentioned flame retardant monomer having at least one double bond (specifically, the flame retardant monomer represented by the chemical formula 1) at a level of less than 10 weight %, less than 8 weight %, less than 6 weight %, less than 5 weight % or less than 3 weight % based on the total weight of the organic-inorganic composite polymer electrolyte, the non-fluidity of the organic-inorganic composite electrolyte can be ensured by also including a structural unit derived from the network polymer structure derivative.

[0073] The structural unit derived from the network polymer structure derivative can contain less than 20 weight %, for example, 1 to 20 weight %, based on the total weight of the organic-inorganic composite polymer electrolyte. By containing the structural unit derived from the network polymer structure derivative in the above range, the non-fluidity and ion conductivity of the organic-inorganic composite electrolyte can be ensured at the same time.

[0074] The flame retardant polymer may contain less than 50% by weight, for example, 2.5 to 50% by weight, based on the total weight of the organic-inorganic composite polymer electrolyte. By containing the flame retardant polymer in the above range, a polymer network can be formed at an appropriate level in the electrolyte, thereby ensuring appropriate non-fluidity without excessive hardening of the organic-inorganic composite electrolyte, and having excellent ionic conductivity and high-rate characteristics of the battery.

[0075] The flame retardant polymer can be based on the total weight of the organic-inorganic composite polymer electrolyte, for example, containing more than 2.5 weight%, more than 3 weight%, more than 5 weight%, more than 7 weight%, more than 10 weight%, more than 15 weight% or more than 20 weight%, and can contain less than 50 weight%, less than 45 weight%, less than 40 weight%, less than 35 weight% or less than 30 weight%.

[0076] The organic-inorganic composite polymer electrolyte disclosed herein includes the flame-retardant inorganic salt as described above. The organic-inorganic composite electrolyte includes the flame-retardant inorganic salt, which can capture H radicals generated by the combustion of the non-aqueous solvent or block oxygen, thereby extinguishing the flame.

[0077] For example, the flame retardant inorganic salt may be a fluoride that generates fluorine free radicals by thermal decomposition, thereby being able to capture H free radicals. Specifically, the fluoride is thermally decomposed during combustion to generate F free radicals, and the F free radicals can provide a function of capturing H free radicals generated by the combustion of the non-aqueous solvent, thereby inhibiting combustion. If expressed by a reaction formula, it is as follows:

[0078] [F]·+H·→[F]H

[0079] As the fluoride mentioned above, it is not limited thereto, for example, it can be an alkali metal, an alkaline earth metal or a metal fluoride, specifically, it can be the alkali metal such as Li, Na, K, Rb, Cs, Fr; alkaline earth metal such as Be, Mg, Ca, Sr, Ba, Ra; transition metals from Group 3 to Group 12; fluorides of Group 13 metals. More specifically, it can be an alkali metal fluoride, and it can be a lithium or sodium fluoride. For example, the fluoride can include LiF, NaF, KF, etc., and more specifically, it can be LiF or NaF.

[0080] In addition, the flame retardant inorganic salt may be an inorganic salt that generates carbon dioxide by thermal decomposition. Carbon dioxide generated by thermal decomposition blocks oxygen, thereby being able to extinguish flames. As the flame retardant inorganic salt described above, carbonate compounds may be cited. When the carbonate compound is burned, it undergoes thermal decomposition to generate CO2 gas as shown in the following reaction formula:

[0081] MCO3→MO+CO2

[0082] The CO2 gas thus generated can block the oxygen near the flame, thereby providing the effect of extinguishing the flame.

[0083] The carbonate compound may be, for example, the fluoride, alkali metal, alkaline earth metal, transition metal of group 3 to group 12; the carbonate compound of group 13 metal may be, more specifically, carbonate of Li or Na. For example, the carbonate compound may be a compound of the alkali metal such as Li, Na, K, Rb, Cs, Fr and CO3, specifically, Li2CO3, Na2CO3, K2CO3, CaCO3, etc., more specifically, Li2CO3, Na2CO3.

[0084] In addition, the solubility of the flame retardant inorganic salt in water may be 1.5 g / 100 ml or less. When the solubility of the flame retardant inorganic salt in water exceeds 1.5 g / 100 ml, the inorganic salt is dissolved in the electrolyte and separated into anions / cations, which may make it difficult to ensure the effect of improving physical properties.

[0085] The organic-inorganic composite polymer electrolyte according to the present disclosure includes the flame-retardant inorganic salt as described above, thereby providing an effect of suppressing the combustion of the non-aqueous solvent, and in addition, by containing them, it can also contribute to suppressing the growth of Li dendrites.

[0086] When the shear modulus of the inorganic substance is 6 GPa or more, as described above, the growth of Li dendrites can be effectively suppressed. In the present disclosure, in order to ensure the flame retardancy of the organic-inorganic composite electrolyte and suppress the growth of Li dendrites, a flame retardant inorganic salt having a shear modulus of 7 GPa or more can be used.

[0087] For example, in the present disclosure, by containing a flame retardant inorganic salt having a shear modulus of 7 GPa or more in a specified content in the organic-inorganic composite electrolyte, the flame retardancy of the organic-inorganic composite electrolyte can be improved while also improving the physical properties, thereby effectively inhibiting the growth of lithium dendrites in the organic-inorganic composite electrolyte.

[0088] Specifically, the organic-inorganic composite electrolyte may include an inorganic salt having a shear modulus of 7 GPa or more and 150 GPa or less, and more specifically, may include an inorganic salt having a shear modulus of 7 GPa or more and 60 GPa or less. The shear modulus may be obtained by a method based on ASTM E143.

[0089] The flame retardant inorganic salt may be contained in an amount of 10 wt % or less based on the total weight of the organic-inorganic composite polymer electrolyte.

[0090] The flame retardant inorganic salt is not limited thereto, and may have a particle size of 5 nm or more and 50 μm or less. The particle size of the flame retardant inorganic salt satisfies the above range, so that when the particle size is less than 5 nm, the volume of the inorganic salt increases and the viscosity of the polymer electrolyte solution before solidification increases, and it may be difficult to ensure uniform dispersion. When the particle size exceeds 50 μm, the inorganic salt particles precipitate, and it may be difficult to ensure uniform dispersion.

[0091] The particle shape of the flame retardant inorganic salt is not particularly limited, and may have various shapes such as spherical, cylindrical, or tubular.

[0092] The organic-inorganic composite polymer electrolyte disclosed herein includes a flame retardant inorganic salt in a flame retardant polymer matrix, and the flame retardant inorganic salt may have a concentration gradient from the surface of the organic-inorganic composite polymer electrolyte to the thickness direction. Specifically, the content of the flame retardant inorganic salt gradually decreases from the surface of the organic-inorganic composite polymer electrolyte to the thickness direction. More specifically, the flame retardant inorganic salt may be locally present on the surface of the organic-inorganic composite polymer electrolyte, for example, the flame retardant inorganic salt may be concentrated in an area within 10% relative to the total thickness of the organic-inorganic composite polymer electrolyte.

[0093] The organic-inorganic composite polymer electrolyte including a flame retardant polymer and a flame retardant inorganic salt provided in the present disclosure includes a flame retardant inorganic salt that provides a function of enhancing physical properties within the matrix of the flame retardant polymer as described above, and further contains an electrolyte solution containing a non-aqueous solvent and a lithium salt as an electrolyte salt.

[0094] The organic-inorganic composite polymer electrolyte can be an organic-inorganic composite polymer electrolyte in the form of a composition obtained by mixing the monomer including at least one double bond, the network polymer structure derivative which can be added as needed, the flame retardant inorganic salt, the non-aqueous solvent and the electrolyte salt, wherein the flame retardant inorganic salt and the non-aqueous solvent electrolyte are dispersed in the flame retardant polymer matrix by polymerizing the monomer.

[0095] On the one hand, it is also possible to first polymerize a composition including the monomer including at least one double bond and the network polymer structure derivative that can be added as needed to produce a flame retardant polymer matrix, and then impregnate an electrolyte including an electrolyte salt and a non-aqueous solvent into the flame retardant polymer matrix, thereby producing an organic-inorganic composite polymer electrolyte through gelation.

[0096] For the polymerization, a polymerization initiator may be included as needed. As long as it is a polymerization initiator commonly used in the manufacture of polymer electrolytes, the polymerization initiator is used without particular limitation. For example, as the polymerization initiator, a peroxide polymerization initiator may be cited, such as tert-butylperoxyneodecanoate (TBND), tert-butylperoxypivalate (TBPP), tert-butylperoxy-2-ethylhexanoate (TBPO), tert-butylperoxy-3,5,5-trimethylhexanoate (TBPIN), azobisisobutyronitrile (AIBN), etc.

[0097] The composition may further include a crosslinking agent. As long as it is a crosslinking agent commonly used in the manufacture of polymer electrolytes, the crosslinking agent is not particularly limited, for example, it may include bisphenol A ethoxylate diacrylate, trimethylolpropane ethoxylate triacrylate (TMPETA), trimethylolpropane triacrylate (TMPTA), trimethylolpropane trimethacrylate (TMPTMA), di-trimethylolpropane tetraacrylate (DTMPTA).

[0098] The method of polymerizing the flame retardant polymer is not particularly limited, and may be performed by thermal polymerization. In this case, the polymerization time may be approximately 30 minutes or more and 24 hours or less, and the thermal polymerization temperature may be 40 to 100°C.

[0099] As long as it is used as an electrolyte salt of a common lithium secondary battery, the electrolyte salt is not particularly limited and can also be used in the present disclosure. As the electrolyte salt, it is not limited thereto, for example, it can be selected from (i) Li + 、Na + , K + and (ii) a cation selected from the group consisting of PF6 - 、BF4 -, Cl - Br - 、I-、ClO4 - 、AsF6 - 、CH3CO2 - CF3SO3 - 、N(CF3SO2)2 - 、C(CF2SO2)3 - The electrolyte salts may be used alone or in combination.

[0100] The non-aqueous solvent is not particularly limited as long as it is used as a common organic solvent for non-aqueous electrolyte, and cyclic carbonates, linear carbonates, lactones, ethers, esters, sulfoxides, acetonitrile, lactams, ketones, and the like can be used.

[0101] Examples of the cyclic carbonates include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), fluoroethylene carbonate (FEC), etc., and examples of the linear carbonates include diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), and methyl propyl carbonate (MPC).

[0102] In addition, as an example of the lactone, γ-butyrolactone (GBL) can be mentioned, as an example of the ether, dibutyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, 1,4-dioxane, 1,2-dimethoxyethane, 1,2-diethoxyethane, etc. can be mentioned, and as an example of the ester, methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, butyl propionate, methyl valerate, etc. can be mentioned.

[0103] In addition, examples of the sulfoxide include dimethyl sulfoxide, examples of the lactam include N-methyl-2-pyrrolidone (NMP), and examples of the ketone include polymethyl vinyl ketone.

[0104] Furthermore, halogenated derivatives of the above-mentioned organic solvents may also be used. Any of these organic solvents may be used alone, or two or more thereof may be used in combination.

[0105] According to the organic-inorganic composite polymer electrolyte disclosed in the present invention, a polymer electrolyte all-solid-state battery can be provided, which includes a flame-retardant inorganic salt in a flame-retardant polymer matrix, an electrolyte solution including an electrolyte salt and a non-aqueous solvent, and the organic-inorganic composite polymer electrolyte. Specifically, the all-solid-state battery can include a positive electrode, a negative electrode, and the organic-inorganic composite polymer electrolyte located between the positive electrode and the negative electrode.

[0106] In the present disclosure, the positive electrode is not particularly limited as long as it is a positive electrode generally used in a secondary battery, and may include, for example, a positive electrode collector; and a positive electrode mixture layer formed on at least one side of the positive electrode collector.

[0107] The composition of the positive electrode current collector is not particularly limited, and a plate or foil made of indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li) or an alloy thereof may be used.

[0108] The positive electrode active material including the positive electrode mixture layer is not particularly limited. As an example, the positive electrode mixture layer as a positive electrode active material may include a lithium-transition metal oxide, for example, a lithium-transition metal oxide such as lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMn2O4) or lithium nickel oxide (LiNiO2), or a lithium-transition metal composite polymer oxide in which a part of these transition metals is replaced by other transition metals. Specifically, the positive electrode active material may be an NCM-type positive electrode active material represented by the following chemical formula 3; or an LLO (Li rich layered oxides, Over Lithiated Oxides, Over-lithiated layered oxide, OLO, LLOs) type positive electrode active material represented by the following chemical formula 4:

[0109]

Chemical formula 3

[0110] Li a Ni b M 1-b O2

[0111] In the chemical formula 3, 0.9≤a≤1.2, b≥0.5, and M is at least one of Na, Mg, Ca, Y, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Co, Fe, Cu, Ag, Zn, B, Al, Ga, C, Si, Sn, Ba, and Zr.

[0112] Specifically, in the chemical formula 3, 0.95≤a≤1.08 may be satisfied, and b may be greater than or equal to 0.6, greater than or equal to 0.8, greater than or equal to 0.8, greater than or equal to 0.9, or greater than or equal to 0.98.

[0113] Specifically, in the chemical formula 3, M may include Co, Mn or Al. More specifically, M includes Co and Mn, and may further include Al according to selection.

[0114]

Chemical formula 4

[0115] Li 1+x M 1-x O2

[0116] In the chemical formula 4, 0≤x≤0.4, and M is at least one of Na, Mg, Ca, Y, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Ni, Mn, Co, Fe, Cu, Ag, Zn, B, Al, Ga, C, Si, Sn, Ba, and Zr.

[0117] Specifically, in the chemical formula 4, M may include Ni, Co, Mn or Al, and more specifically, may include Ni, Co and Mn, and may further include Al according to selection.

[0118] In addition, the positive electrode active material may be a lithium iron phosphate (LFP)-based positive electrode active material represented by the chemical formula of LiFePO 4 .

[0119] In addition, the lithium-transition metal oxide may also be a secondary particle in which a plurality of primary particles are assembled or agglomerated to form substantially one particle, or may be in the form of a single particle. The single particle form may, for example, refer to a secondary particle in which a plurality of primary particles (for example, greater than 10) are assembled or agglomerated to form substantially one particle. However, the single particle form does not exclude the situation in which single particles in the range of 2 to 10 are bonded or closely attached to each other and have a monomer form. In some embodiments, the positive electrode active material may also include both the secondary particle form and the single particle form.

[0120] The positive electrode mixture layer may further include a binder, which may include, for example, one or more of polyvinylidene fluoride, styrene butadiene rubber (SBR), polytetrafluoroethylene, vinylidene fluoride / hexafluoropropylene copolymer, polyacrylonitrile, and polymethyl methacrylate.

[0121] The positive electrode mixture layer may further include a conductive material. As examples, the conductive material may include graphite such as natural graphite or artificial graphite; carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, carbon nanotube (CNT) and other carbon-based materials; metal powder or metal fiber such as copper, nickel, aluminum, silver and the like; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polystyrene derivatives, etc. One or more of the above.

[0122] As long as it is a negative electrode used in a normal secondary battery, the negative electrode is not particularly limited. As an example, it may include a negative electrode current collector; and a negative electrode mixture layer formed on at least one surface of the negative electrode current collector.

[0123] The composition of the negative electrode current collector is not particularly limited, and a plate or foil made of indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li) or an alloy thereof can be used.

[0124] As the negative electrode active material, the negative electrode mixture layer may include carbonaceous active materials such as graphite of artificial graphite or natural graphite; silicon-based active materials such as silicone or silicon oxide (SiOx; 0 < x < 2), Si-C composite, etc.; and metals such as lithium metal.

[0125] The negative electrode mixture layer may further include a binder. As an example, the binder may include one or more of styrene-butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, vinylidene fluoride / hexafluoropropylene copolymer, polyacrylonitrile, polymethyl methacrylate, etc.

[0126] The negative electrode mixture layer may further include a conductive material. As an example, the conductive material may include graphites such as natural graphite or artificial graphite; carbonaceous materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, carbon nanotube (CNT), etc.; metal powders or metal fibers such as copper, nickel, aluminum, silver, etc.; conductive whiskers such as zinc oxide, potassium titanate, etc.; conductive metal oxides such as titanium oxide, etc.; or conductive polymers such as polystyrene derivatives, etc., and one or more of them.

[0127] In the present disclosure, the all-solid-state battery including the organic-inorganic composite polymer electrolyte is such that the organic-inorganic composite polymer electrolyte has a concentration gradient of a flame-retardant inorganic salt. In particular, more of the flame-retardant inorganic salt may be present on the surface in contact with the negative electrode.

[0128] The flame-retardant inorganic salt may have a concentration gradient in which the concentration decreases from the surface toward the central portion with respect to the thickness of the organic-inorganic composite polymer electrolyte. That is, the content of the flame-retardant inorganic salt may be higher on the surface of the electrolyte, and more is present on the surface than at the center when observed in the thickness direction of the organic-inorganic composite polymer electrolyte.

[0129] On the one hand, generally, a SEI (solid electrolyte interface) layer is formed on the surface of the negative electrode by reacting with the electrolyte. This SEI layer formed on the surface of the negative electrode can be regarded as coming from the electrolyte of the present disclosure, and thus can be regarded as a part of the electrolyte.

[0130] Example

[0131] The present disclosure is described in more detail below with reference to the following examples. The following examples are intended to illustrate the present disclosure by way of specific examples, but are not intended to limit the present disclosure.

[0132] Example 1

[0133] -Organic-inorganic composite polymer electrolyte composition-

[0134] The following organic-inorganic composite polymer electrolyte composition was manufactured, that is, as shown in the following Table 1, the phosphorus polymer compound represented by Chemical Formula 1-1, the compound represented by Chemical Formula 2-1 (TMPETA, average molecular weight 428 g / mol), electrolyte, and spherical LiF having a shear modulus of 55.1 GPa based on ASTM E143 were contained in the contents shown in Table 1. In Table 1, each content is weight % of the total weight of the organic-inorganic composite polymer electrolyte composition.

[0135]

Chemical formula 1-1

[0136]

[0137]

Chemical formula 2-1

[0138]

[0139] In the chemical formula 2-1, n is 1.

[0140] The electrolyte is prepared as follows: a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 3:7 contains 1M LiPF6 as an electrolyte salt, and fluoroethylene carbonate (FEC) is added thereto at a content of 10 wt % of the total weight of the electrolyte.

[0141] -Organic-inorganic composite polymer electrolyte-

[0142] The prepared organic-inorganic composite polymer electrolyte composition was thermally cured at 70° C. for 1 hour to produce an organic-inorganic composite polymer electrolyte.

[0143] In order to observe whether the organic-inorganic composite polymer electrolyte has fluidity, after the transparent container containing the organic-inorganic composite polymer electrolyte is placed normally, the transparent container is turned over to observe whether the electrolyte flows, and photographs are taken respectively. Figure 1 At this time, (a) is a photo of the container placed normally, and (b) is a photo of the container placed upside down.

[0144] In order to evaluate the flame retardancy of the organic-inorganic composite polymer electrolyte, the prepared organic-inorganic composite polymer electrolyte was ignited for 1 second using a blowtorch. Then, the time from ignition to extinguishing was measured, and the result was used to calculate the time / electrolyte weight (sec / g) relative to the remaining organic-inorganic composite polymer electrolyte, and thus shown in Table 2 as self-extinguishing time (sec / g).

[0145] Then, Table 2 shows the reduction ratios of the self-extinguishing time of Examples 1 and 2 when the self-extinguishing time of Comparative Example 1 is used as the standard as the reduction ratios relative to the standard.

[0146] -Button battery monomer containing organic-inorganic composite polymer electrolyte-

[0147] The Li electrode with a thickness of 100 μm was cut into a circle with a diameter of 1.6 cm, and the polyethylene separator with a thickness of 20 μm was cut into a circle with a diameter of 1.8 cm.

[0148] After 20 μL (40 μL in total) of the prepared organic-inorganic composite polymer electrolyte composition was added to each side of the separator, the mixture was stacked in a structure of Li / electrolyte solution+polyethylene separator / Li to manufacture a lithium symmetric button cell battery.

[0149] In addition, thermal curing was performed at 70°C for 1 hour to produce an all-solid-state battery with a lithium symmetric button cell monomer structure.

[0150] For the prepared all-solid-state battery, at 1.5 mA / cm 2 The monomer is driven under conditions of 2 h and 150 °C, thereby analyzing the electrodeposition and removal of lithium over time for the lithium symmetric all-solid-state battery.

[0151] As lithium is deposited and removed, the voltage of the button cell is observed over time. Figure 2 The results are shown in the graph of .

[0152] Example 2

[0153] An organic-inorganic composite polymer electrolyte was produced by the same method as in Example 1 except that spherical Li 2 CO 3 having a shear modulus of 8.0 GPa was used instead of LiF having a shear modulus of 55.1 GPa used in Example 1.

[0154] The organic-inorganic composite polymer electrolyte produced was evaluated in the same manner as in Example 1. Figure 1 A photograph of the fluidity is shown in FIG. 1 , and the self-extinguishing time and the reduction ratio relative to the standard are shown in Table 2.

[0155] Furthermore, an all-solid-state battery with a lithium symmetric button cell structure was manufactured by the same method as in Example 1, and the electrodeposition and removal movement of lithium over time were analyzed. Figure 2 The results are shown in .

[0156] Example 3

[0157] An organic-inorganic composite polymer electrolyte was manufactured by the same method as in Example 1, except that the fluorinated polymer compound represented by Chemical Formula 1-2 was used instead of the compound represented by Chemical Formula 1-1 in Example 1.

[0158]

Chemical formula 1-2

[0159]

[0160] The obtained organic-inorganic composite polymer electrolyte was evaluated in the same manner as in Example 1, and the self-extinguishing time and the reduction ratio relative to the standard were analyzed.

[0161] Example 4

[0162] An organic-inorganic composite polymer electrolyte was produced by the same method as in Example 3 except that spherical Li 2 CO 3 having a shear modulus of 8.0 GPa was used instead of LiF having a shear modulus of 55.1 GPa used in Example 3.

[0163] The obtained organic-inorganic composite polymer electrolyte was evaluated in the same manner as in Example 1. Table 2 shows the self-extinguishing time and the reduction ratio relative to the standard.

[0164] Comparative Example 1

[0165] By the same method as in Example 1, a lithium symmetric button cell with a Li / electrolyte+PE separator / Li structure was manufactured using a Li electrode and a PE separator.

[0166] At this time, a lithium symmetrical button cell was manufactured by the same method as in Example 1, except that the electrolyte did not include the compounds represented by the chemical formulas 1-1 and 2-1 but had a composition of 1 M LiPF6-EC / EMC (3 / 7, v / v) + 10 wt % FEC, and no thermal curing process was performed after manufacturing the button cell.

[0167] For the prepared electrolyte battery, at 1.5 mA / cm 2 The monomer was driven under the conditions of 100 μL and 200 μL for 1 hour to analyze the lithium electrodeposition and removal movement over time. Figure 2 The analysis results are shown in .

[0168] Comparative Example 2

[0169] An organic-inorganic composite polymer electrolyte was produced by the same method as in Example 1 except that LiF used in Example 1 was not added.

[0170] The obtained organic-inorganic composite polymer electrolyte was evaluated in the same manner as in Example 1. Figure 1 A photograph of the fluidity is shown in FIG. 1 , and the self-extinguishing time and the reduction ratio relative to the standard are shown in Table 2.

[0171] Furthermore, an all-solid-state battery with a lithium symmetric button cell structure was manufactured by the same method as in Example 1, and the electrodeposition and removal of lithium over time were analyzed. Figure 2 The results are shown in .

[0172] Comparative Example 3

[0173] An organic-inorganic composite polymer electrolyte was produced by the same method as in Example 1 except that spherical Al 2 O 3 having a shear modulus of 152.0 GPa was used instead of LiF having a shear modulus of 55.1 GPa used in Example 1.

[0174] The obtained organic-inorganic composite polymer electrolyte was evaluated in the same manner as in Example 1. Figure 1 A photograph of the fluidity is shown in FIG. 1 , and the self-extinguishing time and the reduction ratio relative to the standard are shown in Table 2.

[0175] Furthermore, an all-solid-state battery with a lithium symmetric button cell structure was manufactured by the same method as in Example 1, and the electrodeposition and removal of lithium over time were analyzed. Figure 2 The results are shown in .

[0176] Comparative Example 4

[0177] An organic-inorganic composite polymer electrolyte was produced by the same method as in Example 1 except that spherical inorganic Ga2O3 having a shear modulus of 76.0 GPa was used instead of LiF having a shear modulus of 55.1 GPa used in Example 1.

[0178] The obtained organic-inorganic composite polymer electrolyte was evaluated in the same manner as in Example 1. Table 2 shows the self-extinguishing time and the reduction ratio relative to the standard.

[0179] Furthermore, an all-solid-state battery with a lithium symmetric button cell structure was manufactured by the same method as in Example 1, and the electrodeposition and removal of lithium over time were analyzed. Figure 2 The results are shown in .

[0180]

Table 1

[0181]

[0182]

Table 2

[0183] Self-destruction time (sec / g) Reduction ratio relative to the standard Example 1 48.5 -42.9% Example 2 49.7 -41.5% Example 3 45.1 -46.9% Example 4 46.3 -45.5% Comparative Example 1 85.0 0.0% Comparative Example 2 73.4 -13.6% Comparative Example 3 69.6 -18.0% Comparative Example 4 70.5 -17.1%

[0184] -Electrolyte fluidity evaluation-from Figure 1 It can be seen that the organic-inorganic composite polymer electrolytes prepared in Examples 1 and 2 and Comparative Examples 2 and 3 all include electrolyte solutions but do not show fluidity, so it can be confirmed that the electrolyte included in each battery is made into a gel or solid state.

[0185] - Fire Extinguishing Performance Evaluation-

[0186] Comparative Example 2 is an electrolyte prepared using only a flame retardant polymer. It can be confirmed that the self-extinguishing time of the electrolyte solution of Comparative Example 1 is shortened by about 18%.

[0187] On the one hand, Comparative Examples 3 and 4, as organic-inorganic composite electrolytes that further include inorganic particles of aluminum oxide and inorganic particles of gallium oxide compared to Comparative Example 2, show that the effect of shortening the self-extinguishing time is not large even if inorganic substances are further included. From this result, it can be confirmed that aluminum oxide (Al2O3) and gallium oxide do not have an effect of improving flame retardancy. In addition, although it is not proposed as a comparative example, it can be confirmed that even if silicon oxide is included, it is similar to aluminum oxide and cannot provide an effect of improving flame retardancy.

[0188] In contrast, the organic-inorganic composite polymer electrolytes of Examples 1 and 2, including the flame retardant polymer of Chemical Formula 1-1, respectively had significantly shortened self-extinguishing times of 48.5 sec / g and 49.7 sec / g, and provided excellent results of reducing the self-extinguishing time by more than 40% relative to the standard.

[0189] In addition, the organic-inorganic composite polymer electrolytes of Examples 3 and 4, including the flame retardant polymer of Chemical Formula 1-2, respectively had self-extinguishing times of 45.1 sec / g and 45.3 sec / g, and provided excellent results of reducing the self-extinguishing time by more than 40% relative to the standard.

[0190] Although not limited to a specific theory, it can be confirmed that the F radicals generated by the thermal decomposition of LiF, an inorganic salt included in the organic-inorganic composite polymer electrolyte, capture the H radicals or OH radicals generated by the thermal decomposition of the non-aqueous solvent, and the CO2 generated by the thermal decomposition of Li2CO3 prevents the reaction with oxygen, thereby providing a fire extinguishing effect.

[0191] From this, it was confirmed that when an inorganic salt capable of releasing F radicals or CO 2 by thermal decomposition together with a flame retardant polymer is included, excellent flame retardancy can be provided.

[0192] -Evaluation of lithium electrodeposition / electrolysis-

[0193] When the electrolytes of Examples 1 and 2 and Comparative Examples 1 to 4 were used, Figure 2 The results of evaluating the electrodeposition and removal of lithium metal are shown in FIG. Figure 2 It can be seen that by observing the order of increase in overvoltage in Li symmetric monomers, in the battery of Comparative Example 1 using a liquid electrolyte, the overvoltage increased before reaching 100 hours, and in the battery of Comparative Example 2 using a polymer electrolyte that does not include inorganic particles, the voltage increase phenomenon occurred at a similar period to Comparative Example 1, but the degree of overvoltage was mitigated.

[0194] On the one hand, in the batteries of Comparative Example 3 using an organic-inorganic composite polymer electrolyte including aluminum oxide as inorganic particles and Example 1 using an organic-inorganic composite polymer electrolyte including LiF as inorganic particles, similarly, the overvoltage increased, and the battery of Example 2 using an organic-inorganic composite polymer electrolyte including Li2CO3 inorganic salt showed the latest increase in overvoltage.

[0195] As described above, the increase in overvoltage indicates the formation of lithium dendrites. From the above results, it can be seen that by adding inorganic salts, such as LiF and Li2CO3 used in the embodiments, with a shear modulus of 8 to 55.1 GPa, the growth of Li dendrites can be inhibited. In addition, it can be confirmed that the efficiency of lithium electrodeposition / removal is further improved.

[0196] From the above results, it is understood that when the alkali metal fluoride or alkali metal carbonate compound proposed in the present disclosure is added, the combustion of the organic-inorganic composite polymer electrolyte can be suppressed while suppressing the growth of lithium dendrites.

Claims

1. An organic-inorganic composite polymer electrolyte comprising a flame retardant polymer and a flame retardant inorganic salt having a shear modulus of 7 to 60 GPa.

2. The organic-inorganic composite polymer electrolyte according to claim 1, in, The flame retardant polymer includes at least one selected from the group consisting of phosphorus-based polymers, phosphazene-based polymers, fluorinated polymers, and ionic polymers.

3. The organic-inorganic composite polymer electrolyte according to claim 2, in, The phosphorus-based polymer includes at least one selected from the group consisting of phosphates, phosphonates, and phosphinates.

4. The organic-inorganic composite polymer electrolyte according to claim 2, in, The phosphorus-based polymer includes a structural unit derived from a compound represented by the following Chemical Formula 1: 【Chemical formula 1】 In the chemical formula 1, L 1 To L 3 are each independently a direct bond; or a substituted or unsubstituted C 1 -C 20 alkyl, R 1 To R 3 Each of them is independent of the other and at least one of them is a functional group having a double bond between carbon atoms, and the others are independently of the other and are hydrogen, a substituted or unsubstituted hydrocarbon group.

5. The organic-inorganic composite polymer electrolyte according to claim 4, in, The R 1 To R 3 Each of the functional groups is independent of the other and at least one of the functional groups is selected from the group consisting of an acrylate group, a methacrylate group, a cyanoacrylate group, an ethylene acrylate group, a vinyl group, an allyl group, and a vinyl ether group.

6. The organic-inorganic composite polymer electrolyte according to claim 4, in, The hydrocarbon group is selected from substituted or unsubstituted C 1 -C 20 Alkyl, substituted or unsubstituted C 2 -C 20 Alkenyl and substituted or unsubstituted C 6 -C 20 Aryl.

7. The organic-inorganic composite polymer electrolyte according to claim 2, in, The phosphazene polymer includes at least one selected from the group consisting of linear phosphazenes and cyclic phosphazenes.

8. The organic-inorganic composite polymer electrolyte according to claim 1, in, The flame retardant polymer further includes a structural unit derived from a network polymer structure derivative having two or more reactive functional groups.

9. The organic-inorganic composite polymer electrolyte according to claim 8, in, The network polymer structure derivative includes a compound represented by the following Chemical Formula 2: 【Chemical formula 2】 In the chemical formula 2, R 4 To R 6 Each independently selected from the group consisting of hydrogen, acrylate, methacrylate, cyanoacrylate, vinyl acrylate, vinyl, allyl and vinyl ether, R 4 To R 6 At least two of the above are selected from the group consisting of acrylate, methacrylate, cyanoacrylate, ethylene acrylate, vinyl and vinyl ether groups, The R 7 is selected from hydrogen, substituted or unsubstituted C 1 -C 20 Alkyl, substituted or unsubstituted C 2 -C 20 Alkenyl and substituted or unsubstituted C 6 -C 20 Aryl.

10. The organic-inorganic composite polymer electrolyte according to claim 1, in, The flame retardant polymer is contained in an amount of 50 wt % or less of the total weight of the organic-inorganic composite polymer electrolyte.

11. The organic-inorganic composite polymer electrolyte according to claim 1, in, The flame retardant inorganic salt generates F free radicals or CO by thermal decomposition. 2 .

12. The organic-inorganic composite polymer electrolyte according to claim 1, in, The solubility of the flame retardant inorganic salt in water is less than 1.5 g / 100 mL.

13. The organic-inorganic composite polymer electrolyte according to claim 1, in, The particle size of the flame retardant inorganic salt is 5 nm to 50 μm.

14. The organic-inorganic composite polymer electrolyte according to claim 1, in, The flame retardant inorganic salt is selected from the group consisting of metal fluorides and carbonate compounds.

15. The organic-inorganic composite polymer electrolyte according to claim 1, in, The flame retardant inorganic salt includes fluoride or carbonate of Li or Na.

16. The organic-inorganic composite polymer electrolyte according to claim 1, in, The flame retardant inorganic salt accounts for less than 10% by weight of the total weight of the organic-inorganic composite polymer electrolyte.

17. The organic-inorganic composite polymer electrolyte according to any one of claims 1 to 16, in, The organic-inorganic composite polymer electrolyte further includes a non-aqueous solvent and a lithium salt. 18 . An all-solid-state battery comprising a negative electrode, a positive electrode, and the organic-inorganic composite polymer electrolyte according to any one of claims 1 to 16 located between the negative electrode and the positive electrode.

19. The all-solid-state battery according to claim 18, in, The organic-inorganic composite polymer electrolyte has a concentration gradient of a flame retardant inorganic salt.

20. The all-solid-state battery according to claim 18, in, The flame retardant inorganic salt is present in a larger amount by weight at the center than at the surface in the thickness direction of the organic-inorganic composite polymer electrolyte.